An Analysis of Grammatical Error of English Students in Writing Skill - Nanning Nanning; Saepuddin; Munawir (Universitas Sulawesi Barat, 2020)
This research was to find out the kinds of grammatical errors made by the students in writing undergraduate theses and to find out the most common error made by the students. The research problem is What were the kinds of grammatical error made by the students in writing undergraduate thesis? And What was the most common grammatical error made by the students in writing undergraduate thesis? The population of this research was the English students’ undergraduate theses. This research used cluster random sampling technique. The researchers chose 20 backgrounds of undergraduate theses as the sample. The result of this research found eight kinds of grammatical error made by the students namely Article, Verb Tense, Subject-Verb Agreement, Singular/Plural, Word Class, Sentence Structure, Spelling, and Punctuation. The most common grammatical error made by the students in writing undergraduate theses is error in Verb Tense with 86 errors (27.65%). The next is Word Class with 55 errors (17.68%), Sentence Structure with 42 errors (13.50%), Article with 37 grammatical errors (11.89%), Punctuation with 28 errors (9%), Singular/Plural with 24 errors (7.71%), Spelling with 21 errors (6.75%), and Subject-Verb Agreement with 18 errors (5.78%).